2021
DOI: 10.1097/ccm.0000000000005141
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Outcomes, and Trends of Patients With Sepsis and Opioid-Related Hospitalizations in U.S. Hospitals*

Abstract: OBJECTIVES: Widespread use and misuse of prescription and illicit opioids have exposed millions to health risks including serious infectious complications. Little is known, however, about the association between opioid use and sepsis. DESIGN: Retrospective cohort study. SETTING: About 373 U.S. hospitals. Patients: Adults hospitalized between January 2009 and Sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 46 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…Hepatitis‐C was also associated with lower risk of sepsis and mortality. This is important, given the relatively high prevalence of both hepatitis‐C and sepsis among patients with OUD, often linked to injection drug use [ 16 ]. Research is mixed on the relationship between hepatitis‐C and COVID‐19, with some studies associating hepatitis‐C with higher mortality [ 35 , 51 ], others finding no effect [ 52 ] and others reporting a protective effect [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatitis‐C was also associated with lower risk of sepsis and mortality. This is important, given the relatively high prevalence of both hepatitis‐C and sepsis among patients with OUD, often linked to injection drug use [ 16 ]. Research is mixed on the relationship between hepatitis‐C and COVID‐19, with some studies associating hepatitis‐C with higher mortality [ 35 , 51 ], others finding no effect [ 52 ] and others reporting a protective effect [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have not examined specific complications of COVID‐19 to which people with OUD may be particularly vulnerable (e.g. kidney failure and sepsis) [ 15 , 16 ]. Moreover, no studies to our knowledge have identified particular characteristics among OUD patients associated with increased risk for COVID‐19 progression and death.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the literature suggests that the prevention of sepsis plays an important role in the care of all types of opioid users. In a US cohort based in 373 hospitals, almost half of the mortality outcomes were associated with sepsis diagnosis ( 50 ). The proportion of sepsis hospitalizations related to opioid use in this cohort increased by 77% between 2009 and 2015.…”
Section: Discussionmentioning
confidence: 99%
“…While more work is needed to characterize the mechanism behind the length of stay changes, our analysis and existing scholarship both suggest that systematic MOUD may also facilitate treatment adherence, leading again to better care for the OUD population. This is particularly important in context of infections stemming from intravenous drug use such as sepsis that require extensive courses of antibiotics for optimal outcomes ( Alrawashdeh et al., 2021 ). Health systems should consider the potential multifaceted benefits of widespread MOUD availability in terms of improved inpatient outcomes and reductions in intensive service utilization.…”
Section: Discussionmentioning
confidence: 99%